2021
DOI: 10.1136/bmjopen-2020-047462
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic disparity in health-related behaviours and dietary habits among public workers in China: a cross-sectional study

Abstract: ObjectiveWe aimed to estimate the distribution of health-related behaviours and dietary habits by sociodemographics among public workers in China.DesignCross-sectional study.SettingA representative sample was obtained from 10 government-run institutions in Hunan province of China.ParticipantsA total of 5029 public workers were included in this study.Primary and secondary outcome measuresPrevalence on their sociodemographic characteristics, health-related behaviours and dietary habits. Socioeconomic status (SES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
0
7
0
1
Order By: Relevance
“…Another study conducted in the US revealed a weaker association between lifestyles and health outcome among men with low incomes, whereas not among women ( 57 ). This difference could be because smoking, heavy alcohol consumption, or physical inactivity behaviors might be more prevalent in men of low SES ( 20 ). Inconsistent definitions of SES and lifestyles also explain the part of the problem.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study conducted in the US revealed a weaker association between lifestyles and health outcome among men with low incomes, whereas not among women ( 57 ). This difference could be because smoking, heavy alcohol consumption, or physical inactivity behaviors might be more prevalent in men of low SES ( 20 ). Inconsistent definitions of SES and lifestyles also explain the part of the problem.…”
Section: Discussionmentioning
confidence: 99%
“…This study was based on the Cohort study on Chronic Diseases of Governmental Employees, which was carried out in five major cities (Changsha, Zhuzhou, Huaihua, Xiangtan, and Changde) of Hunan Province, China. Detailed information on study design of this cohort has been described in our previous study ( 20 ). Briefly, a multistage sampling design was carried out to obtain a representative sample from January 2018 to November 2019, and incidence data were updated to 31 December 2020.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tingkat pendidikan mampu mempengaruhi pola pikir seseorang dalam berperilaku hidup sehat. Hal tersebut berkaitan dengan penggunaan dan pemanfaatan pelayanan kesehatan yang diterimanya (14). Tingkat Pendidikan juga mempengaruhi penggunaan obat maupun perilaku swamedikasi oleh masyarakat (15) (16).…”
Section: Pembahasanunclassified
“…Another study conducted in the US revealed a weaker association between lifestyles and health outcome among men with low incomes, whereas not among women (57). This difference could be because smoking, heavy alcohol consumption, or physical inactivity behaviors might be more prevalent in men of low SES (20). Inconsistent definitions of SES and lifestyles also explain the part of the problem.…”
Section: Discussionmentioning
confidence: 99%